Dietary Supplementation With Magnolia Bark Extract Alters Chicken Intestinal Metabolite Levels - Park, Inkyung; Oh, Sungtaek; Lillehoj, Erik. P.; Lillehoj, Hyun S. (Frontiers in Veterinary Science, 2020)
Magnolia bark extract administered as a dietary supplement to poultry confers a performance and health benefit, but the mechanisms are unknown. Here, a metabolomics approach was used to identify changes in intestinal metabolite levels in chickens fed an unsupplemented diet or a diet supplemented with magnolia bark extract. Total body weight gains of chickens fed magnolia bark-supplemented diets were increased 2% (from 861 to 878 g/chicken), compared with chickens fed an unsupplemented diet. Compared with unsupplemented controls, the levels of 278 intestinal biochemicals (metabolites) were altered (165 increased, 113 decreased) in chickens given the magnolia-supplemented diet. Data for biochemicals of intestinal contents of chickens fed the unsupplemented diet clustered on the left side of the PCA score plot, while those of the magnolia-supplemented diet were separated and clustered on the right side. The biochemicals included changes in the levels of amino acids, fatty acids, peptides, and nucleosides, which provided a distinctive biochemical signature unique to the magnolia-supplemented group, compared with the unsupplemented group. These results provide the foundation for future studies to identify naturally-produced biochemicals that might be used to improve poultry growth performance.